Everything clean? Transfer of DNA traces between textiles in the washtub - Kamphausen, Thomas; Fandel, Sabine Birgit; Gutmann, Jochen Stefan; Bajanowski, Thomas; Poetsch, Micaela (International Journal of Legal Medicine, 2015)
Forensic genetic analysis of items possibly handled by a suspect or a victim is frequently inquired by the law enforcement authorities, since DNA left on touched objects can often be linked to an individual. Due to technical improvement, even poor traces, which seemed to be unsuitable for DNA analysis a few years ago, may be amplified successfully today. Yet, DNA can be transferred to a crime scene artificially or unintentionally without any primary contact between the individual and the object found at the crime scene, the so-called secondary transfer or indirect transfer in general. In this study, “secondary transfer” scenarios with cells and DNA of different origins under wet conditions were investigated. Transfer was simulated as either “washing by hand” in a washtub or as “machine laundry” in a washing machine. As expected, major differences were seen between blood stains and epithelial abrasions. DNA from blood donors could be detected clearly both on the donor and on the acceptor textile, regardless of washing method. Regarding epithelial abrasions, simulating worn clothes, after washing by hand, only little residual DNA was found, and partial profiles were displayed on the donor textile, while transfer to the acceptor textile occurred even less and not in noteworthy amount and quality. Single alleles could be found both on donor textiles and acceptor textiles after simulated machine wash, but no reliable DNA profile could be verified after laundry in machine. Therefore, a DNA transfer from one worn cloth (without blood stains) to another textile in the washing machine seems to be extremely unlikely.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Epithelial abrasions; Low copy number DNA; Secondary transfer; STR; Washing; Washing machine